PENINGKATAN KUALITAS PUPUK ORGANIK CAIR (POC) BERBAHAN DASAR URINE SAPI DENGAN PEMBERIAN MOLASE DAN EM4: SUATU KAJIAN PUSTAKA - K. F., RIYANTO; DUDI, D.; HERNAMAN, I. (Majalah Ilmiah Peternakan, 2024)
The cattle industry in Indonesia is a growing livestock industry and this business has prospective opportunities. The increasing cattle industry in Indonesia will be in line with the waste produced. Ruminant livestock is one of the waste producers that has the potential to disrupt the environment if not managed properly. Utilization of cow feces and urine can be used as an organic fertilizer material that is environmentally friendly and can overcome waste problems. One of the uses of livestock waste is the manufacture of liquid organic fertilizer based on cow urine. Cow urine contains 95% water, 2.5% N and 2.5% other components (minerals, salts, hormones and enzymes). The composition of cow urine indicates that the nutrient content is good. However, the N-organic content of liquid organic fertilizer is very low if there is no improvement in the quality of liquid organic fertilizer. Improvement can be done by adding molase and EM-4 (effective microorganism-4) which contains organic matter that can improve the quality of the fertilizer produced. Liquid organic fertilizer from cow urine base material added with EM4 and molase can improve the quality of liquid fertilizer in terms of total N, C-organic, TDS and pH.